(untitled) (Revista Brasileira de Contabilidade e Gestão, 2025)
Purpose: In the context of the rising trade volume between China and countries in the SADC region, this paper examines the determinants of China-SADC trade. The extended trade gravity model of international trade is used to achieve this analysis. Methods: The study estimates the extended trade gravity model using a panel data analysis on 9 SADC countries over 20 years (2000-2019). This research adopts the FE and RE estimation techniques. The Hausman specification is conducted to determine the appropriate estimation technique between the two. The test picks the FE model whose results are reported. Results: The results show that GDP, availability of natural resources in selected SADC countries, and loan commitments are significant determinants of trade between China and selected countries in the SADC region.